Effects of [Nphe1, Arg14, Lys15] N/OFQ-NH2 (UFP-101), a potent NOP receptor antagonist, on molecular, cellular and behavioural alterations associated with chronic mild stress. (June 2017) - Vitale, Giovanni; Filaferro, Monica; Micioni Di Bonaventura, Maria Vittoria; Ruggieri, Valentina; Cifani, Carlo; Guerrini, Remo; Simonato, Michele; Zucchini, Silvia
The present study investigated the effect of [Nphe 1 ] Arg 14, Lys 15 -N/OFQ-NH2 (UFP-101), a selective NOP receptor antagonist, in chronic mild stress (CMS) in male Wistar rats. NOP receptor antagonists were reported to elicit antidepressant-like effects in rodents. Our aim was to investigate UFP-101 effects on CMS-induced anhedonia and impairment of hippocampal neurogenesis. UFP-101 (10 nmol/rat intracerebroventricularly) did not influence sucrose intake in non-stressed animals, but reinstated basal sucrose consumption in stressed animals from the second week of treatment. UFP-101 also reversed stress effects in forced swimming test and in open field. Fluoxetine (10 mg/kg intraperitoneally) produced similar effects. Moreover, we investigated whether UFP-101 could affect CMS-induced impairment in hippocampal cell proliferation and neurogenesis, and in fibroblast growth factor (FGF-2) expression. Our data confirm that CMS reduced neural stem cell proliferation and neurogenesis in adult rat hippocampus. Chronic UFP-101 treatment did not affect the reduced proliferation (bromodeoxyuridine-positive cells) observed in stressed animals. However, UFP-101 increased the number of doublecortin-positive cells, restoring neurogenesis. Finally, UFP-101 significantly increased FGF-2 expression, reduced by CMS. These findings support the view that blockade of NOP receptors produces antidepressant-like effects in CMS associated with positive effects on neurogenesis and FGF-2 expression. Therefore, NOP receptors may represent a target for innovative antidepressant drugs.